2022
DOI: 10.3390/nursrep12040097
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Nursing Work Life among Nurses in Saudi Arabia: A Descriptive Cross-Sectional Study

Abstract: Background: Quality of working life (QWL) is a multidimensional concept that describes an employee’s satisfaction with several work life elements. Quality of nurse working life is considered as a stepping stone for health services improvement, as it affects job satisfaction which, in turn, affects the performance of nurses. Understanding and investigating the nurses’ quality of work life in Saudi Arabia is needed for improvement actions. Objectives: This study aimed to examine the quality of nursing work life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Shift duration can negatively impact nurses’ quality of work life, as shown by Al Mutair et al, 28 Silveira Teixeira et al, 24 and Wang et al 26 On the other hand, shift rotation has been identified as a factor that can improve nurses’ quality of work life, as noted by Alharbi et al 30 and Lebni et al 31 The study found a significant correlation between nurses’ quality of work life (QWL) and the type of hospital they work in. Nurses in tertiary, general, and teaching hospitals had poorer QWL 26 , 32 compared to those in specialty settings.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Shift duration can negatively impact nurses’ quality of work life, as shown by Al Mutair et al, 28 Silveira Teixeira et al, 24 and Wang et al 26 On the other hand, shift rotation has been identified as a factor that can improve nurses’ quality of work life, as noted by Alharbi et al 30 and Lebni et al 31 The study found a significant correlation between nurses’ quality of work life (QWL) and the type of hospital they work in. Nurses in tertiary, general, and teaching hospitals had poorer QWL 26 , 32 compared to those in specialty settings.…”
Section: Resultsmentioning
confidence: 98%
“… 5 Female nurses were found to have the lowest QWL satisfaction, 24 whereas 32 reported that male nurses had lower QWL compared to female nurses. This systematic literature review also identified additional factors that affect the quality of nurses’ work life, such as marital status, 30–32 nationality, 27 , 28 family, 22 , 28 working in different hospital, 33 having a non-nursing job, 33 and working full-time. 30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucial to ensure that the nurses’ welfare is supported to enhance their professional development, quality of work, and output levels. Emergency Department (ED) nurses, in particular, work in highly demanding environments [ 3 ], where the intensity of work and the level of effort and empathy required are significantly higher. In this unit, the nurses work with patients who are, in most instances, unable to execute their basic hygienic needs and duties [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The links between work life quality and care quality led National Health Authorities (such as the French Health Authority, HAS) to include work life quality (WLQ) as one of the dimensions to be considered in the certification of hospitals and to systematically integrate it into the quality assessment, as observed in other countries [ 1 , 2 , 3 , 4 , 5 ]. Based on the strong and close link between the well-being of patients and the well-being of caregivers, hospitals have implemented actions to improve the work life quality of their employees, which consequently contributes to improving the quality of patient care [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%